Lost letters : translating Milan Kundera's Czech fiction - Woods, Michelle (Trinity College (Dublin, Ireland). Department of Russian & Slavonic Studies, 2002)
The present thesis, Lost Letters: Translating Milan Kundera's Czech Fiction, in com paring the Czech, French and English versions of Milan Kundera's first six prose works, proposes that the original Czech language texts are themselves translations. Banned in his homeland and writing almost exclusively for a foreign readership, translation became central to Kundera’s work, but has been a controversial area of it. Kundera has revised and overseen the French and English translations of his work, in what appears to be an attempt to make these translations more faithful to the original Czech versions. Critics have previously argued that Kundera's translation policy is atavistic, because he has demanded the impossible, ignoring the inevitable linguistic differences which deny the possibility of absolutely faithful translations.
Keywords: Russian, Ph.D.; Ph.D. Trinity College Dublin